Efektivitas Aktivitas Senam Kaki terhadap Penurunan Kadar Glukosa Darah pada Pasien Diabetes Mellitus - Dian Ramadhan; Dheni Koerniawan (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Background: Diabetes mellitus is a metabolic disorder caused by increased blood glucose levels in the bloodstream or hyperglycemia, which is caused by abnormalities in insulin secretion or abnormalities in insulin work. Physical activity can also affect blood sugar levels, one of which is the physical activity of foot exercises which is recommended for people with diabetes mellitus. Objective: To determine the effectiveness of foot exercise activities in reducing blood glucose levels in diabetes mellitus sufferers. Method: The research design used a descriptive method with a nursing process approach with a case study design. This research was carried out by providing foot exercise physical activity intervention for 3 consecutive days. Results: Based on the application of EBP, the results obtained from 3 patients who experienced a decrease in blood glucose levels before and after being given foot exercise therapy, there was an average decrease in P1 of 13.66mg/dL, P2 of 11.66mg/dL, and P3 of 13mg/dL every day. Suggestion: It is hoped that the results of this research can provide insight to diabetes mellitus sufferers in efforts to manage diabetes mellitus with foot exercise physical activity and be able to apply it.